2007
DOI: 10.1063/1.2711163
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of Co-rich nanocrystalline soft magnetic alloys with low coercivity

Abstract: In this study, a series of five nanocrystalline soft magnetic alloys, with compositions equally spaced between (Co0.70Fe0.20Ni0.10)88Zr7B4Cu1 and (Co0.90Fe0.08N0.02)88Zr7B4Cu1, was fabricated by melt spinning and subsequent isothermal annealing. The alloys were annealed at 823 and 1023K for 3600s, and the resulting structure and magnetic properties are reported. X-ray diffraction indicates that 1h isothermal annealing at 823K results in body-centered cubic crystallites in the Fe∕Ni poor alloys and in a mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…10,11 In previous studies by the present authors, the nanocrystallites were found to be ഛ10 nm in diameter for all compositions. 12,13 This suggests that the amorphous phase plays a prominent role in governing the mechanical behavior of the alloys presented in this work.…”
mentioning
confidence: 95%
“…10,11 In previous studies by the present authors, the nanocrystallites were found to be ഛ10 nm in diameter for all compositions. 12,13 This suggests that the amorphous phase plays a prominent role in governing the mechanical behavior of the alloys presented in this work.…”
mentioning
confidence: 95%